MA Defence: â€œTo Fight the Battles We Never Couldâ€: The Militarization of Marvelâ€™s Cinematic Superheroesâ€ - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2016)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; mso-ansi-language:EN-CA;} --> <!--[endif] --> <!--StartFragment--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]>